The Comparison of Reservoir Impoundment Duration between Ground Observation and Satellite Precipitation Product over Karian, Indonesia - Bambang Adhi Priyambodho; Anugerah Tiffanyputri Kristiani; Vittorio Kurniawan; Erma Yulihastin; Rizky Nugraha Putra Herlambang; Lely Qodrita Avia; Haries Satyawardhana; Restu Wigati; Subekti Subekti; Ngakan Putu Purnaditya; Paulus Setyo Nugroho (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The initial filling phase of reservoirs is a critical period that demands close supervision to ensure safety and functionality. During this phase, the dam is slowly filled with water, submerging floodplains until it reaches its intended storage capacity. This process assesses the response of the dam to water filling and its overall safety, with continuous monitoring and evaluation against design standards. The duration and rate of filling depend on several factors, i.e., precipitation, dam height, and hydropower plant sensitivity; thus, precipitation was the prominent driving force. However, as continuous precipitation data, multi-satellite global precipitation maps under the Global Precipitation Measurement near-real-time (GSMaP NRT) satellite products offer an alternative but tend to underestimate or overestimate rainfall values, posing challenges for accurate predictions. Bias correction methods of GSMaP NRT product in the spanning period of 2005–2022 demonstrated in agreement with ground observation data through the application of the artificial neural network (ANN) method to reduce the error bias to produce reliable results. This study highlights the importance of the impoundment period for reservoir sedimentation and overall dam safety. It emphasises the need for accurate precipitation data in reservoir management and recommends rigorous bias correction when using satellite data to substitute ground measurements.